Eficiência volumétrica de reservatórios para aproveitamento de água de chuva em edificações residenciais no Brasil - Luna, Ysa Helena Diniz Morais de (2022)
Nowadays, numerous tools (indexes, equations, efficiencies) have been applied to the design of rainwater harvesting systems (RHS) reservoirs, to make them technically and economically more viable. This thesis aims to present coefficients that allow the analysis of the potential annual usable volume and the tank efficiency used in rainwater harvest in dwellings, called: volumetric efficiency coefficient (VEC), specific volumetric efficiency coefficient (SVEC), and volumetric usable correction coefficient (VUCC). The coefficients were calculated using daily precipitation series, for the entire Brazilian territory, and by geoprocessing, consultative images were elaborated. The VEC expresses the amount of rainwater that can be used in an annual cycle per unit of tank volume and reached higher values for scenarios combining larger catchment areas and smaller tank volumes, showing higher values in the Amazon, central- west and south regions, and lower values in the northeast and southeast regions, following the availability of rainfall. The SVEC was proposed to better compare the volumetric efficiency of tanks in locations with different rainfall, attenuating the effects of precipitation, and it presented higher values in the northeast region, especially in the semi-arid, allowing an improvement in the analysis of volumetric efficiency for locations with low rainfall. In its turn, the VUCC allows to correct the usable volume when calculated using monthly precipitation data, reducing estimating errors in the usable volume in an annual cycle, reaching lower values in the north and northeastern semi-arid regions. However, in the south region, there are higher VUCC values, demonstrating greater relevance in the application and correction of volumes. VEC and SVEC correlate well with the average annual precipitation index. The VUCC showed the highest correlation with the coefficient of variation of the daily rainfall series. The spatialization of the coefficient values, presented as images, proved to be an easy-to-use tool for end consumers of RHS, and the correlations of the coefficients with rainfall parameters allallowpanding the application´s scope the of these coefficients by users outside the territory covered by this study.